Implementation Of Disability Student Assistance At Pgri Argopuro University In Jember: A Descriptive Study Of Strategies, Challenges, And Impacts - Yaum, Lailil Aflahkul; Prystiananta, Nostalgianti Citra; Ahmad, Yasin; Asrorul, Mais (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2025)
This study aims to describe the implementation of a support program for students with disabilities at Universitas PGRI Argopuro Jember by examining the strategies, challenges, and impacts on their learning process and social engagement. A qualitative approach with a descriptive study method was employed, utilizing in-depth interviews, participatory observation, and document analysis as data collection techniques. The findings reveal that academic and social support programs have been implemented through adaptive learning services, peer volunteer assistance, academic affirmative policies, and social activity integration. Despite supportive policies and facilities, challenges remain in terms of limited trained personnel, inadequate campus infrastructure accessibility, and insufficient understanding of inclusive education among lecturers and staff. The program has positively influenced academic comprehension, self-confidence, and social participation among students with disabilities. These findings reinforce the inclusive education theory, emphasizing the importance of collaboration among all campus elements to foster an equitable and inclusive learning environment. Program success relies on sustainable mentoring training, strengthened inclusive policies, and synergy between institutions and external stakeholders.